Studi Geokimia Dan Pemodelan Kematangan Batuan Induk Pada Formasi Plover, Frigate Dan Echuca Shoals Cekungan Bonaparte Bagian Utara - Amaral, Sancho Da costa; Syaifudin, M; Prasetyadi, C (LPPM Akademi Minyak dan Gas Balongan Indramayu, 2021)
Plover Frigate and Echuca shoal formation sediment, which is believed to be one of the major source rocks in north Bonaparte basin. Ditch cutting sample were analyzed using geochemistry analysis and followed maturity modeling. The total oeganic carbon contests of the sediment range from 0,4- 10% TOC. The sample analyzed have vitrinite reflectance in the range of 0.4-2.8 Ro and Tmax value between 350-470 Â°C which indicate that Plover, Frigate and Echuca Shoal sediments contain immature to dry gas organic matter. The sediments are dominated by type I, II, and III kerogen. Typical oil and gas generating potensial is anticipated from the sediment with fairly high hydrogen index (HI) from 50-700 mgHC/gTOC. One dimensional basin modeling was performed to analyze hydrocarbon potential and expulsion history. The source rock of the Plover, Frigate and Echuca Shoal formation at well location is presently at a stage of early to dry gas generation, gas generation with thermal maturity range from 0,5-2.8. North Bonaparte basin have complete petroleum system element, however, time of forming of element is important. Keywords: Analysis source rock, 1D modelling and petroleum system.